Morals in the world-picture - Matzner, Tobias (From the ALWS archives: A selection of papers from the International Wittgenstein Symposia in Kirchberg am Wechsel. Republication by the Wittgenstein Archives at the University of Bergen)

Sicherheit und Demokratie - Matzner, Tobias (Sicherheitsethik)

Privacy enhancement of smart CCTV and its ethical and legal problems - Koch, Heiner; Matzner, Tobias; Krumm, Julia (European Journal of Law and Technology 4 Nr. 2)

The model gap: cognitive systems in security applications and their ethical implications - Matzner, Tobias (AI & SOCIETY)

Design and implementation of a measurement system for automatically measurement of electrical parameters of thermoelectric generators - Petrov, Dmitry; Assion, Fabian; Hilleringmann, Ulrich (MRS Proceedings)
ABSTRACT The continues development of thermoelectric generators causes a permanent improvement of their characteristics. New types of thermoelectric generators can work at temperatures up to 1000 K. With this, special measurement equipment is needed to control the electrical parameters of the new developed specimens. The devices must be tested over the whole range of operating temperatures. For each temperature value a series of electrical measurements has to be performed. To establish the maximal output power of the thermoelectric generators, a load resistor with variable resistance has to be connected to the output of thermoelectric generator. The measurement system should measure the electrical current through the load resistor and the voltage over this resistor to determine the device parameters. A large amount of measurement data have to be collected and processed to evaluate the electrical characteristics of the specimen and to present them in graphical form, suitable for the comparison with others specimens.
Keywords: General Engineering

Formation and Properties of TiSi2 as Contact Material for High-Temperature Thermoelectric Generators - Assion, Fabian; Schönhoff, Marcel; Hilleringmann, Ulrich (MRS Proceedings)
ABSTRACT Thermoelectric generators (TEG) are capable of transforming waste heat directly into electric power. With higher temperatures the yield of the devices rises which makes high-temperature contact materials important. The formation of titanium disilicide (TiSi 2 ) and its properties were analyzed and optimized for the use in TEG. Depending on a direct or an indirect transformation into the C54 crystal structure the process forms a layer with a resistivity of 20-22 μΩcm. Process gases influence the resistivity and result in difference of 20 %. The growing rate of TiSi 2 on silicon dioxide was determined; it shows a strong dependence on the used atmosphere and temperature. A maximum overgrowing length of 30 μm was found.
Keywords: General Engineering

Electrical characterization of rubber mixture sheets based on a coaxial probe method in combination with 3D electromagnetic simulation model - Kanwar, K.; Fischer, C.; Geneiss, V.; Mager, T.; Ballhausen, U.; Hedayat, C.; Hilleringmann, Ulrich (2012 IEEE International Conference on RFID-Technologies and Applications (RFID-TA))

Enhanced event-driven modeling of a CP-PLL with nonlinearities and nonidealities - Hangmann, Christian; Hedayat, Christian; Hilleringmann, Ulrich (2013 IEEE 56th International Midwest Symposium on Circuits and Systems (MWSCAS))

Resistivity reduction in flexible dye sensitized solar cells by UV irradiation and carbon nanotubes - Hilleringmann, Ulrich; Ohms, B.; Kleine, A. (2013 IEEE International Conference on Industrial Technology (ICIT))

Characterization and Analysis of the Hysteresis in a ZnO Nanoparticle Thin-Film Transistor - Vidor, F. F.; Wirth, G.; Assion, F.; Wolff, K.; Hilleringmann, Ulrich (IEEE Transactions on Nanotechnology)
Keywords: Electrical and Electronic Engineering; Computer Science Applications

Design and analysis of UHF RFID tag for a rubber transmission belt based on 3D electrical model - Kanwar, K.; Geneiss, V.; Mager, T.; Scheele, S.; Ballhausen, U.; Hedayat, C.; Hilleringmann, Ulrich (2013 21st International Conference on Software, Telecommunications and Computer Networks - (SoftCOM 2013))

Designing output-power-optimized thermoelectric generators via analytic and finite element method modelling - Assion, F.; Fischer, C.; Schonhof, M.; Hilleringmann, Ulrich; Hedayat, C. (2013 IEEE International Conference on Industrial Technology (ICIT))

Enhanced organic light-emitting diode based on a columnar liquid crystal by integration in a microresonator - Kasdorf, Olga; Vollbrecht, Joachim; Ohms, Benjamin; Hilleringmann, Ulrich; Bock, Harald; Kitzerow, Heinz-Siegfried (International Journal of Energy Research)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Organic Programming of Real-Time Operating Systems - Khaluf, Lial; Rammig, Franz Josef

Organic Real-time Programming - Vision and Approaches towards Self-Evolving and Adaptive Real-time Software - Rammig, Franz Josef; Khaluf, Lial; Montealegre, Norma; Stahl, Katharina; Zhao, Yuhong

Nonlinear modes in binary bosonic condensates with pseudo–spin-orbital coupling - Zezyulin, D.A.; Driben, R.; Konotop, V.V.; Malomed, B.A. (Physical Review A)
We consider an effectively one-dimensional binary Bose-Einstein condensate (BEC) with nonlinear repulsive interactions and linear spin-orbit (SO) and Zeeman-splitting couplings. In the presence of the trapping harmonic-oscillator (HO) potential, we report the existence of even, odd, and asymmetric spatial modes. They feature alternating domains with opposite directions of the pseudospin, i.e., antiferromagnetic structures, which is explained by the interplay of the linear couplings, HO confinement, and repulsive self-interaction. The number of the domains is determined by the strength of the SO coupling. The modes are constructed analytically in the weakly nonlinear system. The dynamical stability of the modes is investigated by means of the Bogoliubov–de Gennes equations and direct simulations. A notable result is that the multi-domain-wall (DW) structures are stable, alternating between odd and even shapes, while the simplest single-DW structure is unstable. Thus, the system features a transition to the complex ground states under the action of the SO coupling. The addition of the Zeeman splitting transforms the odd modes into asymmetric ones via spontaneous symmetry breaking. The results suggest possibilities for switching the binary system between states with opposite (pseudo)magnetization by external fields, and realization of similar stable states and dynamical effects in solid-state and nonlinear-optical settings emulated by the SO-coupled BECs.

Soliton interaction mediated by cascaded four wave mixing with dispersive waves - Yulin, A. V.; Driben, R.; Malomed, B.A.; Skryabin, D.V. (Optics Express)
We demonstrate that trapping of dispersive waves between two optical solitons takes place when resonant scattering of the waves on the solitons leads to nearly perfect reflections. The momentum transfer from the radiation to solitons results in their mutual attraction and a subsequent collision. The spectrum of the trapped radiation can either expand or shrink in the course of the propagation, which is controlled by arranging either collision or separation of the solitons.

Privacy Issues in Public Discourse. The Case of 'Smart' CCTV in Germany - Hälterlein, Jens; Möllers, Norma (Innovation: The European Journal of Social Science Research)

Single-class genera of positive integral lattices - Lorch, David; Kirschmer, Markus (LMS Journal of Computation and Mathematics)
We give an enumeration of all positive definite primitive Z-lattices in dimension n ≥ 3 whose genus consists of a single isometry class. This is achieved by using bounds obtained from the Smith–Minkowski–Siegel mass formula to computationally construct the square-free determinant lattices with this property, and then repeatedly calculating pre-images under a mapping first introduced by G. L. Watson. We hereby complete the classification of single-class genera in dimensions 4 and 5 and correct some mistakes in Watson’s classifications in other dimensions. A list of all single-class primitive Z-lattices has been compiled and incorporated into the Catalogue of Lattices.
Keywords: Computational Theory and Mathematics; General Mathematics

Collective effects in second-harmonic generation from split-ring-resonator arrays - Niesler, Fabian B.; Linden, Stefan; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, Martin (Conference on Lasers and Electro-Optics 2012)
We perform experiments on resonant second-harmonic generation from planar gold split-ring-resonator arrays under normal incidence of light as a function of the lattice constant. Optimum nonlinear conversion occurs at intermediate lattice constants.
Keywords: tet_topic_shg; tet_topic_meta